Monitoring of pyrethroid resistance in Aedes aegypti: first report of double and triple kdr mutations in Buenos Aires Province - Barrera Illanes, Alberto Nicolás (2024)
Background: Dengue is an emerging disease in Argentina due to the colonization of Aedes aegypti, the mosquito vector. Buenos Aires Province is the biggest and most populated district in Argentina, suffering dengue outbreaks of growing magnitude. During epidemic periods, pyrethroid insecticides are used in this country to control adult mosquitoes. Pyrethroid resistance in dengue vectors has been reported worldwide, making it necessary to implement resistance management strategies. The voltage-gated sodium channel is the target site of pyrethroids. Mutations in the gene encoding this protein, called kdr mutations, are usually the molecular cause of pyrethroid resistance in insects. In Ae. aegypti from the Americas, three kdr substitutions were described: V410L, V1016I, and F1534C. The diagnostic of kdr mutations is recommended for the early detection of pyrethroid resistance as well as the consequent planning of evidence-based control policies. Methods: We distributed ovitraps across 16 localities in Buenos Aires Province, collecting 22,123 eggs. A total of 522 mosquitoes were genotyped in positions 1016 and 1534 of voltage-gated channel using multiplex high-resolution melting and/or TaqMan probe methods. A subset of 449 samples was also genotyped by a singleplex high-resolution melting method developed ad hoc and/or Sanger sequencing. Results: We have documented, for the first time to our knowledge in the central region of Argentina, the presence of the 1016Ikdr + 1534Ckdr allele. Additionally, our study reports the first identification of the V410L mutation in central Argentina. These results underscore a growing trend of pyrethroid resistance in Ae. aegypti, fueled by the widespread use of these insecticides.Conclusions: We detected 1016Ikdr + 1534Ckdr and 410Lkdr mutations in central Argentina for the first time and improved the processivity and accuracy of kdr genotyping methods. The results are both a tool for resistance monitoring and a sign of alarm to direct efforts towards finding sustainable methods for vector control to complement or replace pyrethroids. Joint efforts between academia and authorities to develop and implement public policies for vector control are a productive way to transfer scientific results for their application in public health.